TANGGUNG JAWAB YURIDIS ATAS TERJADINYA KERUGIAN PASIEN SEBAGAI AKIBAT KESALAHAN YANG DILAKUKAN OLEH TENAGA KESEHATAN - Fredy Fredy (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACT That the implementation of the paramedic profession such as nurses, birth attendants and midwifery, physiotherapists and others only has the authority and they are not permitted to use their authority as they wish, but first await other profession signals that are not paramedics.That juridical liability will arise if it is not fulfilled the following conditions: The action taken is not based on medical indications; The actions taken are contrary to their knowledge; The actions taken are against the law.That the problem of the procedure of obtaining compensation due to errors can be made through a claim based on default or unlawful acts (civil) and merging of cases (criminal proceedings). Besides these two methods, in practice it is also often done to settle claims or claim for compensation through means of family (deliberation).